Is physical fitness related with in-game physical performance? A case study through local positioning system in professional basketball players - Rodríguez-Fernández, A.; Ramírez-Campillo, R.; Raya-González, J.; Castillo, D.; Nakamura, F. Y. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2023)
The purpose of this study was to investigate the relationship between physical fitness and external load determined by local positioning system (LPS) in a simulated basketball game. Fourteen professional male basketball players performed a lane agility drill, 20-m maximal sprint speed, countermovement jump (CMJ), drop jump, and repeated sprint tests. Player movements during games (two games of 4 × 7 min) were measured using a portable WIMUPRO LPS and six ultra-wideband antennas. Distance covered, and distance covered in different speed zones, accelerations, and decelerations were recorded. The results obtained showed significant relationship between (a) distance at high decelerations (>-2.0 m s-2) and 20-m maximal sprint speed (r = 0.669, p = 0.049); (b) 20-m maximal sprint speed and maximal speed in simulated games (r = 0.576, p = 0.031); (c) CMJ height and sprint distance (>24.1 km h-1) covered in simulated games (r = 0.772, p = 0.001); and (d) high decelerations and 20-m maximal sprint speed (r = 0.669, p = 0.049) and best time in the RSA test (r = -0.731, p = 0.039). Coaches and strength and conditioning coaches must adjust their training to optimize speed and jumping ability, as they are reflected in physical performance in-game. Players who reach higher speeds (i.e. RSAbest and 20-m sprint time) and CMJ height in field tests may be affected by greater deceleration load in specific training and competition (eccentric contraction). Since hamstring muscles suffer great strain during deceleration, they are more prone to injury, thus these players may require a specific training program to decrease performance losses and risk of injury.